E-Procurement Adoption in the Oil and Gas Industry: A Systematic Review Integrating TAM, UTAUT, and IS Success Models - Aufa Laelani Anjali; Hilya Mudrika Arini (Department Industrial Engineering, University of Muhammadiyah Malang, 2026)
The adoption of e-procurement systems in the upstream oil and gas industry remains challenging due to operational complexity, stringent regulatory requirements, and high technological demands. This study investigates the success factors that influence adoption and effectiveness by integrating three theoretical perspectives: the Technology Acceptance Model (TAM), the Unified Theory of Acceptance and Use of Technology (UTAUT), and the DeLone & McLean Information Systems Success Model. A systematic literature review of 62 peer-reviewed articles was conducted to synthesize evidence from user, system, and organizational levels. The results indicate that user acceptance constructs such as perceived usefulness, ease of use, and trust must be complemented by system quality, information accuracy, and user satisfaction, alongside organizational support factors including leadership commitment, infrastructure readiness, and facilitating conditions. Findings demonstrate that fragmented approaches focusing solely on user behavior or system performance are insufficient in the oil and gas sector, where organizational and technical environments critically shape adoption. To address this gap, the study proposes an integrated conceptual framework linking user, system, and organizational dimensions. The framework provides actionable insights for procurement professionals, system developers, and policymakers to enhance digital procurement performance in complex, high-risk contexts.